THE REHABILITATION OF INCARCERATED CHILD OFFENDERS: CHALLENGES FACED BY SOCIAL WELFARE OFFICERS IN ZAMBIA - Muyobela, Tamara Aggie; Strydom, Marianne (Social Work/Maatskaplike Werk, 2017)
A large number of children worldwide are detained. Social workers are rendering services to these children with the aim of rehabilitating them and reducing recidivism. This study aimed to identify the challenges experienced by social welfare officers in the rehabilitation of child offenders in Zambia. It seemed most of the challenges were experienced because of a lack of resources relating to people power, capacity building, trained social workers and facilities. For Zambia to curb the challenges experienced, the custodians of the child justice programmes should strengthen their resources.